Monthly Electricity Usage at Australian Antarctic Division Kingston - SORENSEN, NEIL (hasPrincipalInvestigator); SORENSEN, NEIL (processor); Australian Antarctic Data Centre (publisher)
This indicator is no longer maintained, and is considered OBSOLETE. INDICATOR DEFINITION Records the quantity of electricity, measured in kWh, used in operating the Australian Antarctic Division site and associated facilites including Macquarie 4 Cargo Facility; Mertonvale Circuit Warehouse and Sandfly Warehouse. TYPE OF INDICATOR There are three types of indicators: 1.Describes the CONDITION of important elements of a system; 2.Show the extent of the major PRESSURES exerted on a system; 3.Determine RESPONSES to either condition or changes in the condition of a system. This indicator is one of: PRESSURE RATIONALE FOR INDICATOR SELECTION Effective monitoring of electricity consumption at the Australian Antarctic Division (AAD) provides tangible evidence of appropriate energy management and the achievment of targets under the Commonwealth Government's energy scheme. To allow more effective management of electricity, historical data will be used in calculating maximum demand set-points based on seasonal influences. Maintaining these records provides a database for submitting information to the Whole of Government Energy Reporting (WOGER), an annual requirement for all federal government divisions. DESIGN AND STRATEGY FOR INDICATOR MONITORING PROGRAM Site: The Australian Antarctic Division, Kingston Tasmania. Frequency: Annual report. Quarterly reports for assessing performance over the quarter. Measurement Technique: Data are compiled from the monthly electricity accounts. RESEARCH ISSUES LINKS TO OTHER INDICATORS SOE Indicator 79 - Stormwater outflow composition for the Australian Antarctic Division Headquarters. SOE Indicator 80 - Sewer outflow composition and flow rates for the Australian Antarctic Division headquarters.